Production Of Cellulose Acetate : Effect Of Pretreatments And Acetylation Conditions On Recycled Paper Dust - Loo, Milly Mei Li (2010)
In this study, cellulose acetate was produced from recycled paper dust of carton box (CPD) and tissue paper (TPD) with the aim to extract value from the waste stream and also to maximize and diversify the utilization of recycled cellulose. The quality of the resultant cellulose acetate was compared to the cellulose acetate produced from the commercial dissolving pulp. In order to approach acetylation pulp properties, acid and oxygen-alkaline pretreatment have been carried out on the carton box paper dust. Both the acid pretreatment (which carried out by treating the paper dust in pH 2 sulfuric acid solution for 1 hour at 80˚C) and the oxygen-alkaline pretreatment (which treated the dust in sodium hydroxide solution under oxygen gas pressure (70psi) at 100˚C for 30 minutes), have improved the chemical properties of the paper dust significantly in comparison to CPD. All the cellulose acetates produced were then characterized by determining the degree of substitution (DS), Fourier Transform Infrared (FTIR), Thermal Gravimetric Analysis (TG) and X-ray diffraction (XRD). The DS of cellulose acetate synthesized from dissolving pulp (DP CA), corrugated paper dust (CPD CA) and tissue paper dust (TPD CA) were 2.15, 1.94 and 2.03 respectively. The chemical properties of both pretreated pulps show a better approach to acetylation grade pulp; thus, there is an increment in DS, the degree of crystallinity and the maximum degradation temperature when compared to CPD CA. However, all the cellulose acetates produced showed a lower DS and thermal stability than commercial cellulose acetate (C CA), hence modifications of acetylation procedure have been done with the intention to improve the properties of cellulose acetate.